A study of cerebral blood flow and metabolism in epileptic psychosis using positron emission tomography and oxygen. Issue 3 (March 1985) - Gallhofer, B; Trimble, M R; Frackowiak, R; Gibbs, J; Jones, T
Abstract : Data are presented on four groups using positron tomography and 15 O inhalation. Compared to age-matched volunteer controls, epileptic patients show regions of low blood flow and hypometabolism as found in previous studies. Epileptic psychotic and non-psychotic patients have been compared, and the main differences noted were lower rOER in the psychotic group, especially in frontal, temporal and basal ganglia regions. When a group of psychotic patients receiving neuroleptic drugs was compared to those free of these medications the rOER was higher in the treated sample, and the rCBF fell, significantly in some areas. These data are discussed in the light of other reports of positron tomography in psychosis.